Learning management system through assignment box alert - Noraziah, Ahmad; Azizul, Aziz; Herawan, Tutut; Roslina, Mohd Sidek; Handrizal, M.; Klaib, Mohammad F. J. (Elsevier Ltd., 2011)
Learning Management System (LMS) is software that has been developed for the administration, documentation, tracking, and reporting the educational resources. Assignment Box Alert (ABA) is a type of LMS which has been developed to manage the student in assignment submission. Before the development of ABA, the submission assignments from the students to lecturer have been done manually either through the hardcopy by printing material or softcopy by using the compact disc. The manual system consumes lot of time, besides quite easily being damaged or misplace. In this project, the development of ABA using the Remote Method Invocation has able to manage the assignment submission efficient and effectively. This is due the transferred file by student can be view more systematically by the lecturer, while at the same time the notification from the system remind the student to upload assignment on time.